2008
DOI: 10.1615/critreveukargeneexpr.v18.i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Chondrocytic Gene Expression by Biomechanical Signals

Abstract: Cartilage is a mechanosensitive tissue, which can means that it can perceive and respond to biomechnical signals. Despite the known importance of biomechanical signals in the etiopathogenesis of arthritic diseases, and their effectiveness in joint restoration, little is understood about their actions at the cellular level. Recent molecular approaches have revealed that specific biomechanical stimuli and cell interactions generate intracellular signals that are powerful inducers or suppressors of proinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 45 publications
0
44
0
4
Order By: Relevance
“…The key intervention in the management of OA is exercise therapy [37,38] . It is well known that exercise training affects the articular cartilage metabolism and modifies the cartilaginous structure by a mechanotransduction response [37][38][39] . Biomechanical stimulus generated by dynamic compression, during a moderate exercise, can reduce the synthesis of proteolytic enzymes, regulating the metabolic balance and preventing the progression of the disease [40,41] .…”
Section: Rheumatic Diseasesmentioning
confidence: 99%
“…The key intervention in the management of OA is exercise therapy [37,38] . It is well known that exercise training affects the articular cartilage metabolism and modifies the cartilaginous structure by a mechanotransduction response [37][38][39] . Biomechanical stimulus generated by dynamic compression, during a moderate exercise, can reduce the synthesis of proteolytic enzymes, regulating the metabolic balance and preventing the progression of the disease [40,41] .…”
Section: Rheumatic Diseasesmentioning
confidence: 99%
“…90 A high-magnitude mechanical strain is proinflammatory and initiates cartilage destruction while inhibiting matrix synthesis, both of which are involved in the NF-kB-related signal pathway. 91,92 It has been reported that a low-magnitude mechanical strain inhibits inflammation by suppressing IL-1b and TNFa-induced transcription of multiple proinflammatory mediators involved in cartilage degradation. 91 It is noteworthy, however, that the influences of mechanical stress are not independent; many mechanical and physiochemical factors that are known to affect chondrocytes are inextricably coupled to one another within the cartilage ECM.…”
Section: Biomechanical Strategymentioning
confidence: 99%
“…For example, many tissues are composed of epithelia wherein the cells are polarized along an apical-basal axis defined by the basal location of a collagen-containing extracellular matrix, and linked together with intercellular junctions, thus forming an integrated unit. Mechanical forces (e.g., stretching) experienced by the tissue-and hence by the cells within the tissue-influence the regulatory state within nucleus of each cell by activating latent regulatory proteins [36][37][38]. Finally, the fully formed organism provides systemic hormonal cues that affect the regulatory states of nuclei throughout the body or within specific organs in response to environmental cues (e.g., diet, pheromones, light, temperature etc.…”
Section: A Developmental Paradigm: Sea Urchin Embryogenesismentioning
confidence: 99%